Rabies mortality and morbidity associated with animal bites in Africa: a case for integrated rabies disease surveillance, prevention and control: a scoping review - Seydou Doumbia; Abraham Aseffa; Reinhard Busse; Adane Mihret; Peter Suwirakwenda Nyasulu; Jacqueline Weyer; Rea Tschopp; Samuel Victor Nuvor; Jacques Lukenze Tamuzi; Luke Nyakarahuka; Gideon Kofi Helegbe; Melaku Tefera Gebreyesus; et al. (BMJ Open, 2021)
Objective The objective of this scoping review was to map the current situation and available evidence and gaps on rabies morbidity, mortality, integrated rabies surveillance programmes, and existing prevention and control strategies in Africa.Methods We conducted a systematic scoping review following the Joanna Briggs methodology and Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews checklist. Medline, Embase, CINAHL (EBSCOHost), Scopus, Web of Science and rabies web conferences were used to search for peer-reviewed publications between January 1946 and May 2020. Two researchers reviewed the studies and extracted data based on author (year) and region, study design and data collection duration, participants/comparators, interventions, control conditions/exposures and outcomes (rabies mortality and morbidity) and key findings/gaps/challenges. The results were reported narratively using Arksey and O’Malley’s methodological framework.Results Electronic search yielded 2775 records, of which 43 studies were included. A total of 543 714 bite victims were censored through the included studies. Most of the victims were less than 15 years of age. The studies included rabies morbidity (21) and mortality (15) fluctuating in space and time across Africa depending on countries’ rabies prevention and control practices (16). Others were surveillance (nine studies); surveillance and prevention (five studies); management and control (seven studies); and surveillance, prevention and control (six studies). We found challenges in rabies reporting, existing dog vaccination programmes and post-exposure prophylaxis availability or compliance.Conclusion This study found challenges for dog rabies control and elimination in Africa and the need for a policy to drive the goal of zero dog-transmitted rabies to humans by 2030.This is an open-access article distributed in accordance with the Creative Commons Attribution Non Commercial (CC BY-NC 4.0) license, which permits others to distribute, remix, adapt, build on this work non-commercially, and license their derivative works on different terms, provided the original work is properly cited, appropriate credit is given, any changes made indicated and the use is non-commercial (see http://creativecommons.org/licenses/by-nc/4.0/).